THE EFFECT OF CONFLICT CONTROL, SCHOOL CULTURE, AND WORK MOTIVATION ON TEACHER PERFORMANCE AT MADRASAH IBTIDAIYAH ACEH - Sari, Rita; Zamal, Syahrul; Gunarsih, Tri; Andayani, Wuryan (STAI Asy-Syukriyyah, 2025)
This study aims to partially and simultaneously analyze the influence of conflict control, school culture, and work motivation on teacher performance in madrasah ibtidaiyah Aceh. The research method employed is a quantitative approach. The respondents of the study were 60 teachers of madrasah ibtidaiyah Aceh. The study's sampling technique uses random sampling techniques. The data collection technique was carried out by distributing questionnaires and analysing the research data using multiple regression analysis. The results showed that partially, the three independent variables had an insignificant positive influence on the dependent variables, with t-count value of X1 = 0.362 > 0.05, t-count value X2 = -0.584 > 0.05, and t-count value of X3 = 0.404 > 0.05. However, based on the ANOVA test, it is known that the value of F-count = 6.840 >However, based on the ANOVA test, it is known that the value of F-count = 6.840 > the value of F-table = 2.775, meaning that the three independent variables have a simultaneous positive influence on the dependent variables. It is known that the contribution of the independent variable is 26.8%, and other variables influence the remaining 73.2%. Therefore, it can be concluded that teacher performance in madrasah ibtidaiyah in Aceh is not significantly influenced by conflict control variables, school culture, and work motivation. Still, this study does not disclose other variables that affect teacher performance.